Laju Pertumbuhan Jamur Rhizopus sp. pada Tempe Kacang Hijau (Phaseolus radiatus L.) - Halifah, Pagarra (bionature, 2009)
This research was a descriptive study, which aims to determine the rate of growth of the fungus Rhizopus sp. the green bean tempe. This research was conducted by growing the fungus on PDA medium using fungus inoculum of 1 gram of green beans with tempeh making dilutions, starting from the dilutions 10-2 , 10-3 and 10-4 are plated on a petri dish of 0.1 mL and incubated for 24 hours. Variation of time of fermentation used without fermentation (0 h), 12 hours, 24 hours, 36 hours, 48 hours, 60 hours and 72 hours for each serial dilution. The number of fungi indirectly calculated using the count method bowls. The results of this study indicate that optimum growth is shown in 36 hours fermentation time with the number of colonies on the 10-2 dilution of 69 colonies (6.9 x 103 colonies / g) and 10-3 dilutions of the 27 colonies. While the 10-4 dilution only at the time of fermentation 36, 48 and 60 hours of growth of 2 colonies and each colony 1. The longer the fermentation time decreased the amount of mushrooms.